Room Selling Price Role in Mediation of the Influence of Service Quality on Oyo Rooms Brand Equity in Sleman Area, Yogyakarta - Raissa Puspita; I Ketut Surata; Jaya Ishwari (Politeknik Pariwisata Bali, 2022)
The Special Region of Yogyakarta is relatively safe and comfortable, and the friendliness of its people makes this city much in demand by tourists. The large number of tourists visiting Yogyakarta is one of the reasons that the hospitality industry in Yogyakarta is experiencing rapid development. An increasing number makes business people make online hotel reservations called Virtual Hotel Operators (VHO). One of the VHOs in Indonesia is OYO Rooms, an acronym for On Your Own. This study aims to determine the role of room price in mediating the effect of service quality on the brand equity of OYO Rooms in the Sleman Region, Yogyakarta. The number of samples used in this study was 70, using purposive accidental sampling. Data was collected using the methods of observation, interviews, questionnaires, and documentation, while the analysis technique uses path analysis. The results showed that (1) service quality had a positive effect on room selling prices, (2) service quality had a positive effect on brand equity, (3) selling price had a positive effect on brand equity, and (4) room selling prices significantly mediated service quality and brand equity. Further research can consider other factors than those tested in this study and more varied analyses.